Impacto do açaí antes do exercício sobre os índices geométricos da variabilidade da frequência cardíaca - Koreyasu, Lívia Yumi [UNESP] (2021)
Introduction: Açaí (Euterpe oleracea) has anti-inflammatory, antioxidant, anti-proliferative and cardioprotective effects, also has good results when it comes to physical activity. Therefore, the aim is to verify the heart rate recovery in men, after a maximum effort test, under the influence of açaí supplementation. Methods: 7 healthy, physically active males aged between 18 and 30 years were evaluated. Sedentary, smoker, cardiorespiratory, musculoskeletal, metabolic or other alterations, individuals who use medications that can influence the autonomic nervous system and men who at rest present systolic pressure greater than 130mmHg and diastolic pressure greater than 85mmHg were excluded. The protocol was divided into 2 days with an interval of 7 days, one day with 750 mg of açaí and the other with placebo. The volunteers ingested the capsule 30 minutes before the protocol. 15-minute rest, exercise on a treadmill up to 90% of the maximum HR estimated by age and 60 minutes of recovery. Results: When analyzing the RRtri and TINN indices, the placebo group (G2) showed a slower recovery, when compared to the açaí group (G1). As for the SD1 index, both groups did not show recovery within 60 minutes. Conclusion: The açaí accelerated the autonomic recovery of heart rate after exercise in young eutrophic men.